PENGAWASAN ALOKASI DANA DESA DALAM PEMERINTAHAN DESA - Hasyim Adnan (Al-Adl : Jurnal Hukum, 2016)
Direct election of regional heads allows prospective regional heads to compete directly to become regional heads in local government. The regional government has implemented local democracy if the regional government has held regional head elections. Regional heads can stop or be dismissed according to the provisions of the laws and regulations concerning the Regional Government. Dismissal of regional heads between 2014-2021 in West Java Province, including in the areas of Karawang Regency, Bogor Regency, Sumedang Regency, Cimahi City, Bekasi Regency, Cianjur Regency, Subang Regency, West Bandung Regency, Cirebon Regency and Indramayu Regency which were caused because these regional heads were proven in court to have committed criminal acts of corruption, and some have even been, and are currently carrying out sentences. This study aims to find out the implementation of the dismissal of regional heads in the province of West Java. West Java Province, during seven years, there have been eleven dismissals. Dismissal of regional heads between 2014-2021 in West Java Province in the local government system in Indonesia is still guided by applicable laws and regulations; the dismissal or impeachment of regional heads who are entangled in corruption crimes, then the regional head is temporarily dismissed without having to go through a proposal from DPRD if charged with committing a crime of corruption. The dismissal of the regional head is carried out by the Minister for the regent or mayor; if the regional head is proven to have committed a crime of corruption which, based on a court decision, has permanent legal force, then the regional head can be dismissed without having to obtain a proposal from the DPRD. The Minister for regents and mayors then carried out the dismissal. The dismissal of the regional head who violates the oath/pledge of office should be accelerated in the process of dismissing the decision, and a state institution should be formed in the region that explicitly handles the process of dismissing the regional head so that it does not take too long, and reflects more direct democracy than procedural democracy.